Workload and Burnout among Nursing Staff in Intensive Care Units of Hospitals in Conakry - Donamou J; Touré A; Diallo TS; Camara AY; Yansané MA; Camara ML (EAS Journal of Anaesthesiology and Critical Care, 2026)
Objective: To describe the workload and burnout among intensive care nurses in hospitals in Conakry. Methods: This was a descriptive, multicenter, cross-sectional study conducted from November 1, 2025, to January 31, 2026, in the Anesthesia and Intensive Care Units of Donka University Hospital, Ignace-Deen University Hospital, and the Sino-Guinean Hospital. Nurses working in intensive care for at least six months, present during data collection, and who provided informed consent were included. Results: The study included 92 nurses, most of whom were under 30 years of age, with a mean age of 32.3 ± 6.8 years and a female predominance (sex ratio: 0.38). State-registered nurses (IDE) accounted for 91% of participants, while State-registered nurse anesthetists (IADE) accounted for 9%. A weekly working time exceeding 48 hours was reported by 66.3% of participants, and 76.1% considered staffing levels insufficient. Perceived workload was high among 77.2% of nurses. Hierarchical support was considered moderate or insufficient by 93.5% of participants. Job satisfaction was low among 60.9%, while 56.5% considered leaving the intensive care unit. An impact of work on mental health was reported by 95.7% of nurses. Burnout was present in 46.7% of participants, with high emotional exhaustion in 30.54%, high depersonalization in 26.78%, and low personal accomplishment in 24.69%. The overall NASA-TLX score was 15.95 ± 1.97. Conclusion: Workload and burnout are substantial among intensive care nurses in Conakry, highlighting the need to improve staffing levels, working conditions, and professional support.